COMMUNITY SERVICE EDUCATION TO INCREASE SELF-CARE (PERSONAL HYGIENE) OF PSYCHIATRIC PATIENTS THROUGH A BATAK CULTURAL APPROACH IN THE MEDAN TUNTUNGAN AREA - Grace Mutiara; Aspiati; Devina Cecelina Panjaitan (Jurnal Masyarakat Indonesia (Jumas), 2025)
Mental health is a crucial aspect of human well-being that includes physical, mental, and social dimensions. One of the real impacts of chronic mental disorders such as schizophrenia is the decrease in the deficit self-care of sufferers which causes them to neglect personal hygiene. This community service activity (PkM) aims to increase the understanding, motivation, and skills of psychiatric patients and families (caregivers) regarding the importance of self-care by integrating local cultural values (Batak culture). The method of implementing activities is carried out through health counseling and psychoreligious and cultural assistance in the Medan Tuntungan District area. This intervention involved an academic team from STIKes Darmo Medan with the target audience including outpatient psychiatric patients, caregiver families, Batak traditional leaders, and local health cadres. The evaluation of the activity was carried out by comparing the results of the pre-test and post-test to measure the level of improvement in understanding and skills of the target. The main supporting factor for this activity is the permission from the sub-district apparatus and the strong kinship ties of the Dalihan Na Tolu system in the Batak ethnic community. In conclusion, the synergy between clinical approaches and local wisdom of Batak culture is effective in stimulating the independence of psychiatric patients and reducing the burden of family care in a sustainable manner.